Impact of a reinforcement treatment with acrylate impregnation on the mechanical behavior of black spruce as connector member. (15th June 2017) - Lafond, C.; Blanchet, P.; Galimard, P.; Landry, V.; Ménard, S.
Highlights: An impregnation process for strengthening the wood in the connector area is proposed. The effect of treatment diminish with the increase of the dowel diameter. The treatment has no effect in the perpendicular to grain loading direction. The treatment helps to distribute the strains around the dowel. Abstract: As a previous study has shown, it is possible to increase by 50% the dowel bearing strength of black spruce with an acrylate formulation applied by impregnation. Three diameters of bolts and two orientations of loading were included in this study. The effect of treatment on the dowel-bearing strength appeared to increase while the diameter of bolt decreased. The orientation of loading was significant as the treatment had a major impact in the parallel to grain direction and no impact in the perpendicular direction. With the digital image correlation analysis, an expanded strain field perpendicular to the load direction was observed. The superior embedding capacity would help to reduce the dimensions of the timbers as well as the number of connections required in the building design. With an increase of ductility, wood connections show a safer yielding behavior.